Paracrine effects of mesenchymal stem cells in cisplatin-induced renal injury require heme oxygenase-1 - Zarjou, Abolfazl (American Physiological Society, 2011)
Multipotent mesenchymal stem cells (MSC) have become a popular and promising therapeutic approach in many clinical conditions. MSC are beneficial in animal models of acute kidney injury (AKI), by mediating differentiation-independent paracrine properties, and have prompted ongoing clinical trials to evaluate the safety and efficacy of MSC. Heme oxygenase-1 (HO-1) is induced in response to stress including AKI and has important anti-apoptotic, anti-inflammatory, and proangiogenic properties in these settings. We therefore examined whether HO-1 plays a role in the beneficial effects of MSC in AKI. We isolated MSC from bone marrow of age-matched HO-1(+/+) and HO-1(−/−) mice. Our studies indicate that while differentiation of MSC into osteo- and adipocytic lineages did not differ between cells isolated from HO-1(+/+) and HO-1(−/−) mice, MSC from HO-1(−/−) mice had significantly lower angiogenic potential. Moreover, HO-1(−/−) MSC demonstrated reduced expression and secretion of several important growth and proangiogenic factors (stromal cell-derived factor-1, vascular endothelial growth factor-A, and hepatocyte growth factor) compared with MSC derived from HO-1(+/+) mice. In addition, conditioned medium of HO-1(+/+) MSC rescued functional and morphological changes associated with cisplatin-induced AKI, while the HO-1(−/−)-conditioned medium was ineffectual. Our studies indicate that HO-1 plays an important role in MSC-mediated protection. The results expand understanding of the renoprotective effects of MSC and may provide novel strategies to better utilize MSC in various disease models.